2019
DOI: 10.3389/fendo.2018.00786
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disrupting Chemicals Interfere With Leydig Cell Hormone Pathways During Testicular Descent in Idiopathic Cryptorchidism

Abstract: Cryptorchidism, a frequent genital malformation in male newborn, remains in most cases idiopathic. On the basis of experimental, epidemiological, and clinical data, it has been included in the testicular dysgenesis syndrome and believed to be influenced, together with genetic and anatomic factors, by maternal exposure to endocrine disrupting chemicals (EDCs). Here, we analyze how EDCs may interfere with the control of testicular descent, which is regulated by two Leydig cell hormones, testosterone, and insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…46,47 Endocrine disrupters with both estrogenic and antiandrogenic effects can interfere with the signaling and hormonal function of Leydig cells during testicular descent. [47][48][49] Thus, we suggest that exposure to glyphosate during gestation and lactation can interfere in the production/action or suppression of hormones produced by Leydig cells during the process, leading to the delayed testicular descent observed in GBH-F1 mice. In addition to these data, we found that GBH-F1 mice at PND150 exhibited lower spermatozoa number in the cauda epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Endocrine disrupters with both estrogenic and antiandrogenic effects can interfere with the signaling and hormonal function of Leydig cells during testicular descent. [47][48][49] Thus, we suggest that exposure to glyphosate during gestation and lactation can interfere in the production/action or suppression of hormones produced by Leydig cells during the process, leading to the delayed testicular descent observed in GBH-F1 mice. In addition to these data, we found that GBH-F1 mice at PND150 exhibited lower spermatozoa number in the cauda epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies together with laboratory cryptorchidism models have shown a strong link between testis descent impairment and xenoestrogen exposure. Such exposure is also associated with increased estrogen levels and expression of ER in the undescended testes [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…An experiment on mice showed that BPA increased germ cell apoptosis (54). On the other hand, Fenichel et al did not find a significant increase in bisphenol A in cryptorchid children (55,56). However, mean levels of bisphenol A were higher in nonpalpable compared to palpable gonads.…”
Section: Influence On Cryptorchidismmentioning
confidence: 96%